Glucosinolates profiles in Maca phenotypes cultivated in Peru and China (Lepidium peruvianum syn. L. meyenii). (June 2019) - Meissner, Henry O.; Xu, Lijia; Wan, Wenting; Yi, Fan
Graphical abstract: Highlights: Glucosinolates in Maca ( L . peruvianum syn. L . meyenii ) grown in Peru and China. Glucotropaeolin (GLCT) and m-metoxyGLCT (MGLCT) profiles, contents and ratios. No MGLCT detected in Maca phenotypes cultivated in Shangri-La, China. Red coloured Maca hypocotyls found only in Peru-grown Maca crops. Abstract: HPLC glucosinolate (GCSN) profiles and concentration levels were examined in hypocotyls of the four prime Maca phenotypes ( Lepidium peruvianum synonym L . meyenii ) labelled as "Yellow", "Black", "Red" and "Purple", grown in Peru (Pe) and/or China (Cn). InTrial I, glucotropaeolin (GLCT) and m-methoxyglucotropaeolin (MGLCT) content, and their ratios, was determined in commercial Maca products of Pe origin and compared with similar products declared as of Cn origin. InTrial II, Maca was propagated and cultivated either in Ancash – Peru, according to a traditional single stage planting system, or in Shangri-La – Cn, applying a two-stage Maca planting procedure adopted by Maca growers in Yunnan. Irrespective of the phenotype, in the Pe cultivation system, cylindrical elongated and pointed Maca hypocotyls (H) were harvested in the mixed crop, while disfigured Maca tubers resembling "ginseng-type root" (G) were predominant in the crop harvested in Cn. Two peaks of GLCT and MGLCT were detected in all analysed hypocotyls of the four Maca phenotypes grown in Pe, but only one peak (GLCT) was detected in the Maca phenotypes grown in Shangri-La, Cn. Significantly higher GLCT values were detected in all the Maca phenotypes grown in Cn than in Pe (P < 0.05), with the highest content recorded in the Black and Purple H-shaped while MGLCT was the highest in Yellow G-shaped Cn Maca tubers. Cn-made "Chinese Maca tablets" contained both GLCT and MGLCT. This indicates that Maca imported from Pe could have been used in the formulation - a fact which was subsequently confirmed by the manufacturer.